Motivation And Job Commitment's Role In Project Bonuses And Employee Performance - Kristioni, Revi; Yanuar (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
This article investigates the mechanism underlying the relationship between project bonuses and employee performance by mediating employee motivation and organisational commitment. It is based on two main theories: Maslow's needs theory, which explains motivation, and organisational commitment theory.